Fiscal Policy as a Solution to Involuntary Unemployment - Tanaka, Yasuhito (Ekonomika, 2021)
We show the existence of involuntary unemployment based on consumers’ utility maximization and firms’ profit maximization behavior under monopolistic competition with increasing, decreasing or constant returns to scale technology using a three-periods overlapping generations (OLG) model with a childhood period as well as younger and older periods, and pay-as-you-go pension for the older generation, and we analyze the effects of fiscal policy financed by tax and budget deficit (or seigniorage) to achieve full-employment under a situation with involuntary unemployment. Under constant prices we show the following results. 1) If the realization of full employment will increase consumers’ disposable income, in order to achieve full-employment from a state with involuntary unemployment, we need budget deficit (Proposition 1). 2) If the full-employment state has been achieved, we need balanced budget to maintain full-employment (Proposition 2). We also consider fiscal policy under inflation or deflation. Additionally, we present a game-theoretic interpretation of involuntary unemployment and full-employment. We also argue that if full employment should be achieved in equilibrium, the instability of equilibrium can be considered to be the cause of involuntary unemployment.